RMA-2모형에 의한 하천인자가 수류에 미치는 영향에 관한 연구 - 김윤호; 최윤영; 최정우 (한국수처리학회지, 21(6), 2013)
At the hydraulic model test and RMA-2 model, under the same gradient term, it was observed that the more increasing were the flow ratios, the more increasing were the maximum flow speeds at severe areas of the bends. The outbreak locations of the maximum velocity of flow appeared almost the same. At the hydraulic model test and RMA-2 model, under the same gradient term, it was analyzed that as the bends were steeper, fluctuation ranges of the relative error of observation values and calculation values increased somewhat. In case of the RMA-2 model, the real hydraulic characteristics were well reflected about the fluctuation ranges of the lockage of right and left banks. The river channel sections of analysis are straight and curved line channels, and numbers of piers are one, three, and five, the curved line channels were applied to 30°, 60°, and 90°. And, as shapes of the piers were composed of circles (5m) and ovals (5m×10m), it was set to analyze at the six point of meshes of river channels. When geometric variable values at the data of the river changes were examined, based on the straight line river changes, 1000m length, 120m width, 1/1000 gradient, and 20m×20m grid size were set. And, 100CMS flow rate, and 5m water level were applied. At the analysis results, in case of flow distributions, overall, they decreased as hydraulic structures became more. But, they increased more at the left and right banks of the hydraulic structures than the numbers of the piers were less. After approximately 300m from the hydraulic structures, it appeared that the flow distributions became stable. In case of the water level distributions, before 100m from the location of the hydraulic structures, the synergy effect was the highest value, and water levels decreased somewhat at the piers parts. However, after 200m from the hydraulic structures, it was analyzed that stable water levels of almost no fluctuation ranges appeared. KCI Citation Count: 0